Epigenomic map of human liver reveals principles of zonated morphogenic and metabolic control. Issue 1 (December 2018) - Brosch, Mario; Kattler, Kathrin; Herrmann, Alexander; von Schönfels, Witigo; Nordström, Karl; Seehofer, Daniel; Damm, Georg; Becker, Thomas; Zeissig, Sebastian; Nehring, Sophie; Reichel, Fabian; Moser, Vincent; et al.
Abstract A deeper epigenomic understanding of spatial organization of cells in human tissues is an important challenge. Here we report the first combined positional analysis of transcriptomes and methylomes across three micro-dissected zones (pericentral, intermediate and periportal) of human liver. We identify pronounced anti-correlated transcriptional and methylation gradients including a core of 271 genes controlling zonated metabolic and morphogen networks and observe a prominent porto-central gradient of DNA methylation at binding sites of 46 transcription factors. The gradient includes an epigenetic and transcriptional Wnt signature supporting the concept of a pericentral hepatocyte regeneration pathway under steady-state conditions. While donors with non-alcoholic fatty liver disease show consistent gene expression differences corresponding to the severity of the disease across all zones, the relative zonated gene expression and DNA methylation patterns remain unchanged. Overall our data provide a wealth of new positional insights into zonal networks controlled by epigenetic and transcriptional gradients in human liver. Spatial mapping of genomic programs in tissue cells is an important step in the understanding of organ function and disease. Here, the authors provide a spatially resolved epigenomic and transcriptomic map of human liver and show porto-central gradients in metabolic and morphogen networks and transcription factor binding sites as a basis to better understand liver regeneration and function.